Persistent loss of tyrosine hydroxylase immunoreactivity in the substantia nigra after neuroleptic withdrawal - Mazurek, M. (BMJ Group, 1998)
A 37 year woman developed neuroleptic induced parkinsonism that persisted long after the drug had been discontinued. This prompted a study of the effect of an eight week course of haloperidol (HAL) followed by two week withdrawal, on dopaminergic neurons of the substantia nigra in rats. Animals treated with HAL showed a highly significant 32%-46% loss of tyrosine hydroxylase (TH) immunoreactive neurons in the substantia nigra, and 20% contraction of the TH stained dendritic arbour. Neuroleptic drug induced downregulation of nigral dopaminergic neurons may help to explain the persistent parkinsonism found in many patients after withdrawal of medication.